Combination Usage of AdipoCount and Image-Pro Plus/ImageJ Software for Quantification of Adipocyte Sizes - Hu, Yepeng; Yu, Jian; Cui, Xiangdi; Zhang, Zhe; Li, Qianqian; Guo, Wenxiu; Zhao, Cheng; Chen, Xin; Meng, Meiyao; Li, Yu; Guo, Mingwei; Qiu, Jin; et al. (Frontiers in Endocrinology, 2021)
In recent decades, the prevalence of obesity has been rising. One of the major characteristics of obesity is fat accumulation, including hyperplasia (increase in number) and hypertrophy (increase in size). After histological staining, it is critical to accurately measure the number and size of adipocytes for assessing the severity of obesity in a timely fashion. Manual measurement is accurate but time-consuming. Though commercially available adipocyte counting tools, including AdipoCount, Image-Pro Plus and ImageJ were helpful, limitations still exist in accuracy and time-consuming. In the present study, we introduced the protocol of combined usage of these tools and illustrated the process with histological staining slides from adipose tissues of lean and obese mice. We found that the adipocyte sizes quantified by the tool combination were comparable as manual measurement while the combined methods were more efficient. Besides, the recognition effect of monochrome segmentation image is better than that of color segmentation image. Overall, we developed a combination method to measure adipocyte sizes accurately and efficiently, which may be helpful for experimental process in laboratory and also for clinic diagnosis.